Study on the Interactions Between Lathyrus (Lathyrus sativus L.) and Agro-climatic Factors to Generate Weather Based Yield Forecasting Models - Ghosh, Argha; Khan, Safiuddin Ahmed (International Journal of Bio-resource and Stress Management, 2019)
A fieldexperiment was conducted with Lathyrus sativus L. sown on nine different dates at weekly interval to study the effect of weather parameters on yield and to develop regression equations involving agro-climatic factors to predict the yield. The experiment was carried out in rabi seasons in 2016-2017 in Instructional Farm, Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India. Simple correlation study between yield and weather parameters was conducted. Yield forecasting models were developed by stepwise regression technique. Highest biomass (4799.5 kg ha-1) was produced by the crops sown on 16th November while biomass yield was the lowest (2524.0 kg ha-1) in the crops sown on 21st December. Mean relative humidity during vegetative phase was positively correlated with grain yield (0.84*). On the contrary grain yield was negatively influenced by vapour pressure deficit at morning (-0.68*) and at afternoon (-0.88**) during reproductive phase. Mean air temperatures exhibited significant negative correlation during reproductive (-0.89**) and maturity phase (-0.86**) with biomass yield. Grain yield could be predicted by morning vapour presure at reproductive phase, heliothermal unit at maturity phase and maximum air temperature at pre-flowering phase with 99.9% predictability. Two models were developed to predict grain yield at the end of vegetative phase with 55.2% and 85.2% predictability respectively. It was clear from the experiment that yield of Lathyrus was significantly influenced by agro-climatic factors and weather parameters can be effectively used to predict yield before harvest.